Insurance risks management methodology - Kartashova Olga Ivanovna; Molchanova Olga Vladimirovna; Axana Turgaeva (Journal of Risk and Financial Management, 2018)
The purposes of the study are to substantiate the influence of the specific features of insurance on the set of management accounting objects and to develop a mechanism of preparing the relevant information for insurance risk management. Management accounting allows generating reports, specially prepared for managers of various levels of control (in contrast to financial accounting, which considers information on the basis of general accounting rules). This allows realizing the main goal of management accounting; that is, providing information support for management decisions aimed at maximizing the organization's profits. The object of research is management accounting in the information system of an insurance company. The stages in the execution of accounting procedures in a management accounting system are defined in the form of a diagram, the features of insurance affecting the organization of management accounting are classified, and an intracompany ledger of the connection between the segments of activity and responsibility centers is developed for insurance companies.
Keywords: 330; operational management; accounting entities; variable and fixed costs; insurance premium; insurance indemnity; the severity of loss